Knowledge and Expectations of Perinatal Care Among Pregnant Women During the COVID-19 Pandemic - Lim, Caleb Chun Wei; Goh, Marlene Samantha Sze Minn; Chua, Ka-Hee; Seet, Meei Jiun; Tay, Siew Guek; Mathur, Manisha; Kong, Juin Yee; Yeo, Kee Thai (Frontiers in Global Women's Health, 2022)
Introduction This study aimed to investigate the knowledge and expectations of pregnant women on perinatal care during the coronavirus disease 2019 (COVID-19) pandemic. Methods A cross-sectional survey was conducted among pregnant women ≥21 years, without a history of confirmed COVID-19, attending antenatal clinics between August and September 2020 via a secure online platform. The survey consisted of 10 questions which evaluated the knowledge and expectations on perinatal and neonatal care during the current pandemic. Results A total of 313 pregnant women completed the survey. The mean age of the participants was 30 years (SD 4; range 22–43 years). The median gestational age was 25 weeks (range 4–40 weeks). The participants were predominantly multiparous (54%) and almost all (98%) had completed secondary level education. Majority of participants were aware of the spread of COVID-19 by respiratory secretions and contact (90%), and the importance of prevention strategies (94%). Up to 72% agreed or strongly agreed that in-utero transmission of SARS-CoV-2 was possible. Most were unsure of the optimal mode of delivery (77%) and only 22% believed that breastfeeding was safe in a pregnant woman with active COVID-19. Although 46% were concerned about increased transmission risk with antenatal clinic visits, only 37% were agreeable to teleconferencing of clinic appointments. Maternal age >35 years was significantly associated with agreement with separation of mother-infant after birth [AOR 1.89 (95% CI 1.05, 3.39)], restrictions of visitors during the postnatal period [1.92 (1.05, 3.49)] and having their confinement practices were affected [2.3 (1.26, 4.17)]. Pregnant women who were multiparous disagreed that breastfeeding was safe in women with active COVID-19 [0.42 (0.23, 0.75)]. Conclusions There was significant uncertainty about the optimal delivery method and safety of breastfeeding with COVID-19 among expectant mothers, along with variable agreement with alterations to routine perinatal care.